Central obesity and hypertension among rural adults of Paschim Medinipur, West Bengal, India - Chanak, Mahua; Bose, Kaushik (Anthropological Review, 2019)
Obesity is generally classified into generalized obesity (BMI ≥30 kg/m2) and abdominal or central obesity (WC ≥90 cm for men and WC ≥80 cm for women) based on World Health Organization recommendation for Asians. Hypertension is one of the most common obesity-related complications, and about 30% of hypertensive individuals can be classified as being obese. The present study aimed to investigate the effect of different age groups (years) on the anthropometric and derived variables. It determined the correlation between anthropometric and derived variables and also estimated the frequency of central obesity and hypertension. Finally, it investigated the relationship between central obesity and blood pressure among rural Bengalee adults of Dirghagram village of Ghatal Block, Paschim Medinipur, West Bengal, India. The present cross-sectional study was undertaken among 310 rural adults (154 males; 156 females) aged over 18 years. Our study was carried out during March, 2017. Height (cm), weight (kg), waist circumference (cm), hip circumference (cm) and blood pressure (systolic and diastolic) were measured using standard procedures. One way ANOVA analysis on most of the anthropometric and derived variables showed a statistically significant increase from younger to older age group in both sexes (p<0.001;p<0.01; p<0.05). In addition to that, more females had central obesity using waist circumference (55.8% vs. 19.5%), waist hip ratio (87.2% vs. 35.7%), waist height ratio (73.7% vs. 44.2%), and conicity index (87.2% vs. 57.8%) criteria, and hypertension (52.5% vs. 27.3%). The prevalence of central obesity was much higher in case of hypertensive individuals. Therefore, the present study showed a high prevalence of central obesity among the rural adults of Dirghagram village. Furthermore, central obesity contributed in increasing hypertension among the villagers.